Pulmonary Embolism With Deep Vein Thrombosis Pasca Negleted Injury Genue Sinistra - Wijayanti, MD, Ayu Putri; Adheriyani, MD FIHA, Revi; Nugroho, MD FIHA, Dhani Tri Wahyu; Riza, MD FIHA, M Faishal; Basworo, MD FIHA, Adityo (Jurnal EduHealth, 2024)
Pulmonary embolism is an infarction of lung tissue due to blockage of the pulmonary artery due to an embolic event. Pulmonary Embolism and Deep Vein Thrombosis have the same pathological process. Pulmonary embolism usually originates from a thrombus dislodged from the deep venous system of the lower extremities. In this case study, a 43-years-old woman with present palpitations, dyspnea, dizziness, suddenly syncope, palpation genue sinistra erytema, tenderness, painful, pitting edema, superficial collateral veins without sign of infection. She after fell from a motorbike and taken to Sangkal Putung for a massage therapy. After this, she just stay in bed (imobilisation) more than 5 week. In physical examination, Heart rate 148 beats/minute. Blood preasure of 100/70 mmHg. Decreased ventilation on oxygen saturation 92% with reservoir mask oxygen. In palpation genue sinistra erytema, tenderness, painful, pitting edema, superficial collateral veins without secondary infection. Chest x-rays present of atelectasis in lobus pulmonum dextra. An electrocardiogram present sinus tachycardia, Q wave followed by an inversion of the T wave in lead III accompanied by an S wave in lead I, P pulmonary, New right bundle branch block, Right ventricular strain with inversion T waves in leads V2 to V3. In Pulmonary angiogram examination there is occlusion of the pulmonary artery branch. From clinical diagnosis and physical examination Deep Vein Thrombosis are applied in the form of Well score 75% and Pulmonary embolism probability high risk with geneva score > 60%.